2013
DOI: 10.3389/fphys.2013.00029
|View full text |Cite
|
Sign up to set email alerts
|

Carotid baroreflex responsiveness in normotensive African Americans is attenuated at rest and during dynamic leg exercise

Abstract: Evidence suggests differences between African Americans (AAs) and Caucasian Americans (CAs) in cardiovascular responsiveness to physiological stressors. This study tested the hypothesis that carotid baroreflex (CBR) control of heart rate (HR) and blood pressure is reduced in AAs compared to CAs during exercise. Mean arterial pressure (MAP) and HR were continuously recorded at rest and during leg cycling in 23 non-hypertensive male subjects (12 AA; 11 CA; age 19–26 years). CBR control of HR and MAP was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…No subject had a history or symptoms of cardiovascular or pulmonary disease. There is compounding evidence to show that sex, age, and race influence carotid baroreceptor function (Credeur et al 2014;Fisher et al 2007Fisher et al , 2009Fisher et al , 2012Holwerda et al 2001Holwerda et al , 2013Kim et al 2011). Thus, in an effort to minimize these variables, each individual with MS was matched to a healthy control of the same sex, age, race, height, and weight.…”
Section: Subjectsmentioning
confidence: 99%
“…No subject had a history or symptoms of cardiovascular or pulmonary disease. There is compounding evidence to show that sex, age, and race influence carotid baroreceptor function (Credeur et al 2014;Fisher et al 2007Fisher et al , 2009Fisher et al , 2012Holwerda et al 2001Holwerda et al , 2013Kim et al 2011). Thus, in an effort to minimize these variables, each individual with MS was matched to a healthy control of the same sex, age, race, height, and weight.…”
Section: Subjectsmentioning
confidence: 99%
“…Regarding carotid baroreflex function, whereby acute baroreflex-mediated HR and MAP responses to simulated hypotension and hypertension at the carotid baroreceptors are assessed, Holwerda et al identified smaller MAP and HR decreases in response to acute carotid hypertension at rest in black than white adults (49,50). These authors also reported a smaller MAP increase in response to acute carotid hypotension at rest in black than white adults in one, but not both, of their recent studies (49,50), with the reason for these discrepant findings remaining unclear. The implication of these findings is that healthy young black adults have a reduced ability to withdraw sympathetic neural outflow to the heart and vasculature and/or restore cardiac parasympathetic activity to "correct" an acute hypertensive stimulus.…”
Section: Autonomic and Cardiovascular Values At Restmentioning
confidence: 99%
“…An important note regarding these existing observations is that most studies involved only male volunteers. Of 19 studies, 11 included only men (4,24,32,34,45,49,50,88,91,94,95), 2 included only women (48,59), and only 6 included both men and women (12,17,25,87,90,92). Given the clinical significance of understanding neural control of cardiovascular function in both men and women, and considering the greater incidence and prevalence of cardiovascular and renal diseases in black adults, it is imperative that future studies in this area involve both male and female volunteers to provide data that can uncover the potential physiological mechanisms underlying the increased cardiovascular risk in this population.…”
Section: Autonomic and Cardiovascular Values At Restmentioning
confidence: 99%
“…Notably, the majority of work contributing to our knowledge of the arterial baroreflex in humans during exercise has been performed in young Caucasian men. In this research topic, Holwerda et al (2013) have begun to extend these findings to young African Americans clearly showing for the first time a similar magnitude of resetting in this group compared to young Caucasian Americans. However, impairments in the ability of African Americans to defend against a hypertensive challenge were observed during steady-state exercise, providing novel information that may begin to explain the greater cardiovascular responsiveness to physiological stressors in African Americans compared to Caucasian Americans.…”
mentioning
confidence: 92%